(untitled) - SAHIL PATIL (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Medical Tourism is a developing exercise of crossing global borders to discover health care. It includes recreation, entertainment and relaxation as well as health and wellness. Medical Tourism in India is growing rapidly & numerous private hospitals are doing their best to take advantage of this opportunity. With a focus to scrutinize the scope of different aspects of medical tourism in India and to figure out the external factors influencing the Indian medical tourism, this paper is an attempt to evaluate the possibilities of Medical Tourism in India and identify the challenges occurring.In line with the objective of analysing the diversity of medical tourism in India this research article continues to discuss literature reviews on the topic and to clarify the research methods used followed by conclusion.